Trans-becomings in western ‘classical’ singing: An intra-active approach - Leppänen Taru; Tiainen Milla (Society for Artistic Research, 2022)
This exposition is an attempt to think transgender experiences and existence in relation to voice and particular musical practices. A key source of inspiration for this voice- and music-centred line of exploration is our collaboration with Finnish singer and voice teacher Demian Seesjärvi. Thus, the propositions made here are meant to take form or reverberate in-between Seesjärvi’s vocalizations, his spoken and written reflections on his body/voice and artistic activity, and the research interests and concepts that we bring into these encounters.